2002
DOI: 10.1246/cl.2002.154
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Lipase-catalyzed Enantioselective Acylation under Reduced Pressure Conditions in an Ionic Liquid Solvent System

Abstract: Lipase-catalyzed transesterification was demonstrated using methyl esters as acyl donors under reduced pressure in an ionic liquid ([bmim]PF6) solvent system. The transesterification of 5-phenyl-1-penten-3-ol took place smoothly under reduced pressure at 27 hPa at 40 °C when methyl phenylthioacetate was used as acyl donor in [bmim]PF6, and we succeeded in obtaining the corresponding acylated compound in optically pure form; this makes it possible to use lipase repeatedly because there was no drop in the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…65 Hence, the effects of ionic liquid reaction media on the resolution of the arylalkanols 20-31 (see Scheme 2) in the presence of, mainly, CaLB and PcL have been investigated. 33,107,108,113,205,206 Vinyl acetate was almost universally adopted as the acyl donor.…”
Section: Lipases and Esterasesmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Hence, the effects of ionic liquid reaction media on the resolution of the arylalkanols 20-31 (see Scheme 2) in the presence of, mainly, CaLB and PcL have been investigated. 33,107,108,113,205,206 Vinyl acetate was almost universally adopted as the acyl donor.…”
Section: Lipases and Esterasesmentioning
confidence: 99%
“…113 A loss of activity was observed, which was ascribed to the accumulation of inhibiting acetaldehyde oligomers in the ionic liquid phase. 205 In [BMMIm][BF4], polymer formation did not take place, presumably because the slightly acidic position at C-2 in the imidazolium ring is blocked. 111 The ionic liquid phase containing the biocatalyst could now be recycled five times without significant activity loss.…”
Section: Catalyst Recyclingmentioning
confidence: 99%
“…The separation of products from enzyme-ILs phase can be facilitated by the inherently low vapour pressure of ILs allowing for easy removal of volatile substances. Thus, products isolation can be carried out by sublimation or distillation [47]. However, such methods are too energetically intensive for application on larger scale.…”
Section: Fig (5)mentioning
confidence: 99%
“…Itoh et al [77] have demonstrated the kinetic resolution of some allylic alcohols in ionic liquid media under reduced pressure. An efficient enzymatic pathway has been developed for the synthesis of enantiopure allylic alcohols from corresponding ␣,␤-unsaturated ketones in this laboratory by employing onepot reduction followed by lipase-mediated resolution protocol in high enantiopurity (Scheme 17) [78].…”
Section: Resolution Of Allylic Alcoholsmentioning
confidence: 99%